Laser sintering of tungsten carbide cutter shafts with integrated cooling channels - Josef, Tomas (2018)
Long lifetime, low wear and high dimensional accuracy are essential requirements for tools in the metal processing industry. High temperatures in the interaction zone between tool and component are harmful and lead to premature malfunction and imprecise processing results. To counteract these, cemented carbides are utilized with suitable properties in terms of stiffness and strength. Furthermore, the lubricants and coolants are used to reduce the temperature to a tolerable degree and to create suitable conditions for the machining. To guarantee an efficient fluid transport, tools include transport channels. These are difficult to achieve with conventional manufacturing methods. Additive manufacturing opens up new possibilities for implementing cavities with almost any shape. This paper presents the design of carbide cutter shafts and their manufacturing. The course and cross-section of channels are optimally designed for the requirements of the process zones to be cooled. The additive production by powder bed based laser sintering required a definition of the process parameters scanning speed, layer thickness and hatch distance that was adapted to the cemented carbide. This is supported by extensive materials characterization methods such as light and electron microscopy, qualitative and quantitative microstructure analysis and mechanical tests (bending strength, Young’s modulus, hardness, fracture toughness). The results are used to correlate process parameters, microstructure development and properties. The objective is to create a parameter set suitable to manufacture tungsten carbide cobalt hard metal parts with similar properties than conventionally produced hard metals. The cutter shafts produced by the additive process have a diameter of 16 mm and will be equipped with brazed cutting inserts in a further process step.